Center-Pivot-Irrigated Popcorn Cost-Return Budget - Dumler, Troy J.; Henson, Darl W. (My University, 1998)
This publication outlines the expected costs and returns for center-pivot-irrigated popcorn in Kansas.
MF996_1998_10
Keywords: MF996; Economics; Crops; MF